“La lateralidad en el desarrollo de la lectoescritura en el nivel de preparatoria de la parroquia Pilaló, cantón Pujilí, provincia de Cotopaxi” - Tipan Vela, Mayte del Rocio (2023)
This research project aims to demonstrate the incidence of laterality in reading and writing development through playful strategies at the high school level. In addition, the possible influence of other factors was analyzed, such as the family environment and previous exposure to reading and writing. The research methodology was framed in the qualitative approach; as an instrument, the thematic analysis method was used to understand the process based on the inquiry and analysis of the information obtained; the applied research instruments were the interview and observation sheet. Based on the results, it was concluded that laterality is essential for the reading-writing process in high school students since by not adequately developing reading-writing, problems arise in school performance, especially in children who do not present well-defined laterality, one of the possible causes is the little knowledge that teachers have about the subject. For this reason, implementing playful strategies that facilitate the reading-writing process is recommended.